Laser desorption/ionization mass spectrometry of L-thyroxine (T-4) using combi-matrix of alpha-cyano-4-hydroxycinnamic acid (CHCA) and graphene - Noh, Joo-Yoon; Kim, Moon-Ju; Park, Jong-Min; Yun, Tae-Gyeong; Kang, Min-Jung; Pyun, Jae-Chul (SPRINGER INTERNATIONAL PUBLISHING AG, 2022)
An optimal combi-matrix for MALDI-TOF mass spectrometry was presented for the analysis of L-thyroxine (T-4) in human serum. For the selection of the optimal combi-matrix, several kinds of combi-matrices were prepared by mixing the conventional organic matrix of CHCA with nanomaterials, such as graphene, carbon nanotubes, nanoparticles of Pt and TiO2. In order to select the optimal combi-matrix, the absorption at the wavelength of laser radiation (337 nm) for the ionization of sample was estimated using UV-Vis spectrometry. And, the heat absorption properties of these combi-matrices were also analyzed using differential scanning calorimetry (DSC), such as onset temperature and fusion enthalpy. In the case of the combi-matrix of CHCA and graphene, the onset temperature and fusion enthalpy were observed to be lower than those of CHCA, which represented the enhanced transfer of heat to the analyte in comparison with CHCA. From the analysis of optical and thermal properties, the combi-matrix of CHCA and graphene was selected to be an optimal combination for the transfer of laser energy during MALDI-TOF mass spectrometry. The feasibility of the combi-matrix composed of CHCA and graphene was demonstrated for the analysis of T-4 molecules using MALDI-TOF mass spectrometry. The combi-matrix of CHCA and graphene was estimated to have an improved limit of detection and a wider detection range in comparison with other kinds of combi-matrices. Finally, the MALDI-TOF MS results of T-4 analysis using combi-matrix were statistically compared with those of the conventional immunoassay.